2014
DOI: 10.1007/s00232-014-9651-2
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Ion Transport and Mucin Expression Following Acrolein Exposure

Abstract: The vocal fold epithelium is exposed to inhaled particulates including pollutants during breathing in everyday environments. Yet, our understanding of the effects of pollutants on vocal fold epithelial function is extremely limited. The objective of this study was to investigate the effect of the pollutant acrolein on two vocal fold epithelial mechanisms: ion transport and mucin synthesis. These mechanisms were chosen as each plays a critical role in vocal defense and in maintaining surface hydration which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…An untreated, sham challenge (PBS alone) was included as a control. Similar challenges have been utilized previously to investigate the adverse effects of clinically relevant insults on the vocal fold epithelial barrier and were specifically chosen for the purpose of the current investigation because these were hypothesized to reduce epithelial viability. Although the concentration of acrolein and pH of HCl is representative of what occurs in vivo, a lower concentration of H 2 O 2 has been used in previous studies in the vocal folds to mimic physiologic conditions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An untreated, sham challenge (PBS alone) was included as a control. Similar challenges have been utilized previously to investigate the adverse effects of clinically relevant insults on the vocal fold epithelial barrier and were specifically chosen for the purpose of the current investigation because these were hypothesized to reduce epithelial viability. Although the concentration of acrolein and pH of HCl is representative of what occurs in vivo, a lower concentration of H 2 O 2 has been used in previous studies in the vocal folds to mimic physiologic conditions .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, we tested whether three clinically relevant challenges would reduce viability as measured by epithelial metabolic activity and cell membrane integrity as compared to an untreated, sham challenge. Challenges included: acrolein, an environmentally pervasive pollutant; hydrochloric acid, the acidic component of laryngopharyngeal reflux; and hydrogen peroxide, a common reactive oxygen species . We hypothesized that these assays would detect reductions in epithelial viability following challenges as compared to sham.…”
Section: Introductionmentioning
confidence: 99%
“…There is some research on the effects of acrolein exposure to the larynx. In excised porcine vocal folds, acute acrolein exposure reduced epithelial sodium ion transport, induced lipid peroxidation, and impaired epithelial integrity and barrier function . However, in vivo studies are needed to fully understand the mechanisms underlying pathological changes from specific pollutant exposures such as acrolein.…”
Section: Introductionmentioning
confidence: 99%
“…In excised porcine vocal folds, acute acrolein exposure reduced epithelial sodium ion transport, induced lipid peroxidation, and impaired epithelial integrity and barrier function. 14,15 However, in vivo studies are needed to fully understand the mechanisms underlying pathological changes from specific pollutant exposures such as acrolein. The underlying mechanisms for acrolein-induced inflammation in the distal airway have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This epithelial barrier can be adversely affected by pollutants found in ciagarettes. 912 Though no study has investigated the effect of CNTs on vocal fold epithelium, CNTs are reported to reduce epithelial resistance in a tracheobronchial epithelial cell line. 13 Fibroblasts are the most common cell type in the vocal folds and are important for synthesizing extracellular matrix (ECM) components such as collagen and elastin.…”
Section: Introductionmentioning
confidence: 99%